2016
DOI: 10.1161/circresaha.115.307878
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Expression of a Dominant-Negative TGF-β Type II Receptor in the Posterior Left Atrium Leads to Beneficial Remodeling of Atrial Fibrillation Substrate

Abstract: Rationale Fibrosis is an important structural contributor to formation of atrial fibrillation (AF) substrate in heart failure (HF). TGF-β signaling is thought to be intricately involved in creation of atrial fibrosis. Objective We hypothesized that gene-based expression of dominant-negative type II TGF-β receptor (TGF-β-RII-DN) in the posterior left atrium (PLA) in a canine HF model will sufficiently attenuate fibrosis induced changes in atrial conduction and/or restitution to decrease AF. Since AF electrogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 75 publications
0
41
0
1
Order By: Relevance
“…TGF‐β1 is involved in the processes of pulmonary fibrosis and liver fibrosis 24, 52. A previous study demonstrated that constitutive expression of dominant‐negative TGFβRII in the posterior left atrium resulted in a significant decrease in atrial fibrosis via inhibition of the TGF signalling pathway and attenuated fibrosis‐induced changes in atrial conduction and restitution to decrease AF 27. The increased level of TGFβRII in the TGF‐β1 group showed that TGFβRII may participate in TGF‐β1‐induced fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…TGF‐β1 is involved in the processes of pulmonary fibrosis and liver fibrosis 24, 52. A previous study demonstrated that constitutive expression of dominant‐negative TGFβRII in the posterior left atrium resulted in a significant decrease in atrial fibrosis via inhibition of the TGF signalling pathway and attenuated fibrosis‐induced changes in atrial conduction and restitution to decrease AF 27. The increased level of TGFβRII in the TGF‐β1 group showed that TGFβRII may participate in TGF‐β1‐induced fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…For rhythm control in paroxysmal AF, however, suppression of ectopic foci in the pulmonary veins would be an ideal target, yet the pulmonary veins do not fit a common coronary distribution. In preclinical models, one typical method is to inject the vector into the myocardium, and then electroporate the tissue to improve DNA uptake (27,28). One could envision a similar delivery system via a catheter at locations that are currently treated with ablation lesions.…”
Section: Myocardial Gene Deliverymentioning
confidence: 99%
“…A central feature of age-related fibrosis is up-regulation of transforming growth factor beta (TGF-β) (48). Kunamalla et al (27) attempted gene-therapy-based modulation of atrial fibrosis by delivering a dominant-negative type II TGF-β receptor to the posterior left atrium in a canine model of AF. The therapy resulted in decreased fibrosis and a reduction in pacing-induced AF in the treated versus control animals (27).…”
Section: Targets For Gene Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Zhang's group found that miR-206 modulated intrinsic cardiac autonomic nerve remodeling in AF via right atrial tachypacing via the regulation of superoxide dismutase 1 (SOD1) in vivo, and this may be a potential therapeutic target for AF because it shortens the atrial effective refractory period [10]. Furthermore, many loci or target genes associated with ion channels, autonomic innervation, gap junctions, and substrate modifiers have been identified in preclinical studies to attenuate fibrosis, autonomic nerve sprouting, and AF duration [11][12][13]. However, inflammation and the immune response, oxidative stress, and genetic mechanisms do not fully explain the development of AF, and autonomic system dysfunction may exert direct effects on the initiation and maintenance of AF due to heterogeneous changes in the atrial electrophysiology [14,15].…”
Section: Introductionmentioning
confidence: 99%